The spice diet : use powerhouse flavor to fight cravings and win the weight-loss battle - Allen, Judson Todd; Reverand, Diane (New York : Grand Central Life & Style, 2018)
"Celebrity chef Judson Todd Allen presents the diet that helped him lose 160 pounds, featuring 60 guilt-free recipes packed with powerhouse flavor created especially for THE SPICE DIET. When Steve Harvey wanted to get camera-ready before his hit television show launched, he turned to Chef Judson Todd Allen to help him. While enjoying the flavorful food Chef Judson prepared, Steve Harvey lost 30 pounds and has kept them off. Chef Judson's diet plan is heaven for food lovers. Using the principles of food science, he offers a way to eat that feels indulgent as it satisfies food cravings and reduces appetite. His program will not only help readers break their addiction to unhealthy foods without feeling deprived but will also inspire them to get into the kitchen to prepare irresistable, healthy meals. THE SPICE DIET provides a full weight-loss program that includes meal plans, creative spice blends, easy-to-prepare recipes, and a heaping helping of motivation"--
Keywords: Weight loss -- Popular works; Cooking (Herbs); HEALTH & FITNESS / Diets; COOKING / Specific Ingredients / Herbs, Spices, Condiments